2016
DOI: 10.1177/0306624x16651903
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Substance Use in Commission of Sexual Crimes and Offense Characteristics Among Youth: Mitigating Effects of Substance Use Treatment

Abstract: The small extant research base on substance use and youth sexual offending has very few descriptive details. Furthermore, research has yet to test associations between the use of substances in the commission of sexual crimes and offense-related characteristics and how substance use treatment can mitigate these effects. In a sample of residentially housed youth adjudicated of a sexual crime ( N = 332), prevalence patterns are broken down by type of substance use behavior. Sequential regression models are run to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 79 publications
(101 reference statements)
0
3
0
1
Order By: Relevance
“…Other studies have identified additional adversity risk factors for youth sexual violence, although between-group differences are not as pronounced. Those who commit sexual crimes often have family risk factors including substance abuse (Levenson & Grady, 2016; Yoder & Caserta, 2018), mental health concerns (Levenson & Grady, 2016), as well as a family criminal history or incarceration (Levenson & Grady, 2016; Wanklyn et al, 2012). Oftentimes, such risks are not categorically different between youth who commit sexual and non-sexual crimes and are often experienced at similarly high rates in both groups (Seto & Lalumiere, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies have identified additional adversity risk factors for youth sexual violence, although between-group differences are not as pronounced. Those who commit sexual crimes often have family risk factors including substance abuse (Levenson & Grady, 2016; Yoder & Caserta, 2018), mental health concerns (Levenson & Grady, 2016), as well as a family criminal history or incarceration (Levenson & Grady, 2016; Wanklyn et al, 2012). Oftentimes, such risks are not categorically different between youth who commit sexual and non-sexual crimes and are often experienced at similarly high rates in both groups (Seto & Lalumiere, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, family members of youth who commit sexual crimes have been found to have co-occurring mental health concerns (Chaffin et al, 2006;Ryan, 2010). Furthermore, substance abuse occurs at higher rates among some family members of youth who commit sexual offenses (Graves et al, 1996;Yoder & Caserta, 2016). Research has also identified family criminal history as a correlate to youthful sexual offending (Ryan, 2010b;Wanklyn, Ward, Cormier, Day, & Newman, 2012).…”
Section: Family Risk and Resiliencymentioning
confidence: 99%
“…As researchers have conclusively found certain trauma experiences (i.e., sexual and physical abuse) to be discriminating risks, there is a need to focus on how these experiences co-occur with other childhood adversity to contribute to concomitant risks for the commission of sexual harm. For example, there are additional adversity risk factors that increase the likelihood for the commission of sexual harm, including family or household problems like mental health, substance use, witnessing violence, or criminality (Levenson & Grady, 2016; Wanklyn et al, 2012; J. Yoder & Caserta, 2016).…”
Section: Introductionmentioning
confidence: 99%